Review of the monograph by V. S. Kruglyk "The system of training of future software engineers for the professional activity at higher educational institutions" - Lazariev, Mykola; Sushchenko, Andrii; Yeremieiev, Volodymyr (Ukrainian journal of educational studies and information technology, 2020)
In the publication the scientific-theoretical and methodological monographic study of V. S. Kruglyk "The system of training of future software engineers for the professional activity at higher educational institutions" has been analyzed, the study reflects the author conceptual approach to the scientific understanding of the problem of training software engineers for professional activities. The structure and content of the monograph have been analyzed; the scientific novelty of the research which consists in the development and substantiation of the author pedagogical system of training future software engineers for their professional activity and the structure of professional competence of a software engineer has been highlighted.